Copying Strategies in People with Different Time Perspectives - Kolchik, E. Yu (Вестник Кемеровского государственного университета, 2022)
The article defines the concepts of time perspective and vision of the future, as well as the relationship between them. A review of foreign and domestic publications revealed the main approaches to adversity, copying, and various classifications of protective behavior. The study involved 49 women and 35 men aged 24–54 y.o., who found themselves in a difficult life situation: all respondents had to leave their permanent place of residence because of a direct threat to their life and health. The empirical research used R. Lazarus’s methodology for diagnosing the copying strategies and F. Zymbardo’s time perspective method. The copying strategies appeared to correspond to different time perspectives. The respondents with a negative past fixation chose confrontation, social support, escape, and avoidance. The respondents with a positive past fixation preferred to plan their problem solutions. The respondents who focused on the present turned to social support and positive reassessment. Those focused on the future accepted their responsibility, planned their solutions, and were prone to positive reassessment. The results were statistically confirmed using the Mann-Whitney U-test. Time perspective proved to be an important intrapersonal resource in psychotherapeutic work with disadvantaged patients.